Low-dose irradiation of nontransformed cells stimulates the selective removal of precancerous cells via intercellular induction of apoptosis. - Portess, D; Bauer, G; Hill, M; O'Neill, P (2007)
An important stage in tumorigenesis is the ability of a precancerous cell to escape natural anticancer signals imposed on it by neighboring cells and its microenvironment. We have previously characterized a system of intercellular induction of apoptosis whereby nontransformed cells selectively remove transformed cells from coculture via cytokine and reactive oxygen/nitrogen species (ROS/RNS) signaling. We report that irradiation of nontransformed cells with low doses of either high linear energy transfer (LET) alpha-particles or low-LET gamma-rays leads to stimulation of intercellular induction of apoptosis. The use of scavengers and inhibitors confirms the involvement of ROS/RNS signaling and of the importance of transformed cell NADPH oxidase in the selectivity of the system. Doses as low as 2-mGy gamma-rays and 0.29-mGy alpha-particles were sufficient to produce an observable increase in transformed cell apoptosis. This radiation-stimulated effect saturates at very low doses (50 mGy for gamma-rays and 25 mGy for alpha-particles). The use of transforming growth factor-beta (TGF-beta) neutralizing antibody confirms a role for the cytokine in the radiation-induced signaling. The system may represent a natural anticancer mechanism stimulated by extremely low doses of ionizing radiation.